Minimal Residual Disease After Autologous Stem-Cell Transplant for Patients With Myeloma: Prognostic Significance and the Impact of Lenalidomide Maintenance and Molecular Risk. Issue 25 (1st September 2022) - de Tute, Ruth M.; Pawlyn, Charlotte; Cairns, David A.; Davies, Faith E.; Menzies, Tom; Rawstron, Andy; Jones, John R.; Hockaday, Anna; Henderson, Rowena; Cook, Gordon; Drayson, Mark T.; Jenner, Matthew W.; et al.
Abstract : PURPOSE: Minimal residual disease (MRD) can predict outcomes in patients with multiple myeloma, but limited data are available on the prognostic impact of MRD when assessed at serial time points in the context of maintenance therapy after autologous stem-cell transplant (ASCT) and the interaction between MRD and molecular risk. METHODS: Data from a large phase III trial (Myeloma XI) were examined to determine the relationship between MRD status, progression-free survival (PFS), and overall survival (OS) in post-ASCT patients randomly assigned to lenalidomide maintenance or no maintenance at 3 months after ASCT. MRD status was assessed by flow cytometry (median sensitivity 0.004%) before maintenance random assignment (ASCT + 3) and 6 months later (ASCT + 9). RESULTS: At ASCT + 3, 475 of 750 (63.3%) patients were MRD-negative and 275 (36.7%) were MRD-positive. MRD-negative status was associated with improved PFS (hazard ratio [HR] = 0.47; 95% CI, 0.37 to 0.58 P < .001) and OS (HR = 0.59; 95% CI, 0.40 to 0.85; P = .0046). At ASCT + 9, 214 of 326 (65.6%) were MRD-negative and 112 (34.4%) were MRD-positive. MRD-negative status was associated with improved PFS (HR = 0.20; 95% CI, 0.13 to 0.31; P < .0001) and OS (HR = 0.33; 95% CI, 0.15 to 0.75; P = .0077). The findings were very similar when restricted to patients with complete response/near complete response. Sustained MRD negativity from ASCT + 3 to ASCT + 9 or the conversion to MRD negativity by ASCT + 9 was associated with the longest PFS/OS. Patients randomly assigned to lenalidomide maintenance were more likely to convert from being MRD-positive before maintenance random assignment to MRD-negative 6 months later (lenalidomide 30%, observation 17%). High-risk molecular features had an adverse effect on PFS and OS even for those patients achieving MRD-negative status. On multivariable analysis of MRD status, maintenance therapy and molecular risk maintained prognostic impact at both ASCT + 3 and ASCT + 9. CONCLUSION: In patients with multiple myeloma, MRD status at both ASCT + 3 and ASCT + 9 is a powerful predictor of PFS and OS.